Fluid Antenna System for 6G: When Bruce Lee Inspires Wireless Communications - Wong, Kai-Kit; Tong, Kin-Fai; Zhang, Yangyang; Zhongbin, Zheng (Electronics letters, 2020)
Since its inception, multiple-input multiple-output (MIMO) has become a magical technology that continues to break new grounds and deliver the needed upgrades in mobile communications. The emerging 5G systems are also being labelled by many as the massive MIMO generation. This somewhat oversimplified view is perhaps a reflection of the great impact MIMO has had on our generation of mobile communication networks. Although the technologies have evolved in the past decades, the principle remains the same—to exploit the diversity of different copies of signals at independent locations for reducing the degree of fading and randomness of wireless channels. Through signal processing and coding, the diversity has been translated successfully into capacity gain and enhancement in other forms of the quality-of-service. This article identifies “fluid” antenna as a trending technology that may succeed MIMO and become a reality to transform wireless communications to a new height. Fluid antenna is a radical approach that advocates software-controlled position-flexible shape-flexible antenna. The concept liberates antennas to unleash massive diversity inherent in the small space of a mobile device and makes possible new opportunities that were previously unthinkable. This article attempts to be imaginative and aims to take readers on a short journey of what fluid antenna might bring in future-generation mobile communications systems and speculate on its impact.